112k views
1 vote
Consider the equation 3p – 7 + p = 13. What is the resulting equation after the first step in the solution?

p – 7 = 13 – 3p
2p – 7 = 13
3p – 7 = 13 – p
4p – 7 = 13

User Bardo
by
5.5k points

2 Answers

4 votes

Answer:

4p - 7 = 13

Explanation:

User Alon Catz
by
5.5k points
3 votes

Answer:

4p - 7 = 13

Explanation:

The first step of the solution should be to simplify the left side by combining like terms. In this case, 3p and p are the like terms and 3p + p = 4p so the answer is 4p - 7 = 13.

User HydraHatRack
by
5.6k points